PENGARUH TRADING VOLUME, MARKET VALUE, DAN RETURN VARIANCE PADA BID-ASK SPREAD - Mas Widhyawati, I Gusti Ayu; Eka Damayanthi, I Gusti Ayu (E-Jurnal Akuntansi; Vol 10 No 3 (2015), 2015)
The purpose of this study was to examine the effect of trading volume, market value, and return variance on bid-ask spread value in the stock split corporate. The sample of this study used purposive sampling method and consisted of 28 companies in 2010-2013. This study used double linier regression to analyze. The empirical results of the study show that trading volume has negative effectsignificantly on bid-ask spread. This showed that the higher of stock traded, the value of the bid-ask spread would be even lower. Market value had significant negative effect on bid-ask spread. This showed that the higher of closing price, bid-ask spread’s value would be even lower. Return variance had no effect on bid –ask spread. This showed that the higher of stock risk, the value of bid-ask spread would not be even higher.
Keywords: bid-ask spread, trading volume, market value, return variance, stock split